ナンキョク リュツォ・ホルム ワン ニ オケル Ice Algae ノ ヒョウカ カンサツ - 佐々木, 洋; ササキ, ヒロシ; 渡辺, 研太郎; ワタナベ, ケンタロウ; Sasaki, Hiroshi; Watanabe, Kentaro (1984)
P(論文) 1983年1月, 南極リュツォ・ホルム湾定着氷域において, スキューバ潜水法を用いて, 定着氷下のice algaeの直接観察を行った。その結果, 海氷下面において, 著しい水平的な不均一分布が認められた。また, 海氷下面に付着するice algaeは容易に脱落すること, 場所によっては海氷底部自体も壊れやすいなどの事実から, ice corerを用いて採取された氷柱サンブルによる現存量の測定には, 定量的な問題が含まれることが示唆された。 Heterogeneity in the horizontal distribution of standing stock of ice algae was observed by the SCUBA divings in January 1983,in a fast ice area of Lutzow-Holm Bay, Antarctica. Colonies of ice algae easily came off from the undersurface of sea ice due to the mechanical disturbances from the ice corer and from water movements caused by a diver. The bottom layer of sea ice was here and there fragile as the substratum of ice algae and was susceptible to disturbances. Based on the observations, the accuracy in the estimation of standing stock of ice algae was discussed. departmental bulletin paper